A relação com a linguagem escrita na inclusão escolar de uma criança com deficiência visual: mediação pedagógica e (im)possibilidades de ensino-aprendizagem - Carvalhais, Keuri Costa [UNIFESP] (2015)
This work deals with the relation between children with visual disability [hereafter named under the acronym DV ? translator?s note], and written language in a school inclusion policy during the first year of elementary school, together with specialized educational attendance [hereafter named under the acronym AEE ? translator?s note]. It aims to discuss the conditions and ways it is accomplished within such educational contexts, and within situations which objective is to introduce children(in)directly to both reading and writing practices, its teaching and learning as well. The investigation is based on Vygotsky?s cultural-storic Psychology (1897-1943), a current of thought that assumes both writing and language as social practices, emphasizing their role on the constitution of cultural functions, and in the school development of children. It also aims to outline the moderator role of the other and that of the language, and the importance they give to the use of cultural instruments towards the development of forms of psychological measures within the existence of any kind of disability. Carried out a case study throughout participant observation, this research was developed with a six-year-old boy with diagnosticated visual disability [hereafter named under the acronym DV ? translator?s note], enrolled in the 1st year of elementary public school, in the city of Guarulhos/SP, and beneficiated by the specialized educational attendance (AEE).During the elaboration of the case study, it was also made semi-structured interviews with the research participants: an AEE?s teacher, a teacher from the elementary school?s classroom, her trainee, the school committee, the visual disabled child, and his mother. The data analysis, carried out under the focus of cultural-storic Psychology outlines the mediation of the teachers ? ways and devices to achieve the pedagogical work that involves the approach towards writing and its learning ? indicating it as preponderant to the construction of the (im)possibilities related to DV children and written language, its learning and development.